ESENSI DAN DAMPAK LIBERALISASI PERDAGANGAN PADA SUBSEKTOR PERKEBUNAN - REDA SUSILA, WAYAN; ANTARA, MADE (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 1 Februari 2004, 2012)
As one of the traded goods and important sub-sectors in Indonesia, estate-crop subsector cannot avoid various strategic business environment changes, mainly related to trade liberalization issues. These changes have been perceived to have significant impacts on the sub-sector. In line with this issue, the main objective of this paper is to assess the likely impacts of trade liberalization with emphasizing on the Indonesian estate crops sub-sector. The results of the study indicates that impacts of the trade liberalization on the subsector in the international markets have been varied, due to the different level of market distortions, level of commitments to reduce distortion, and consistency in implementing the commitments. In general, trade liberalization is expected to lift international prices, while the impacts on production, consumption, and trade have been varied, depending on the crops and countries. Moreover, Indonesia estate crops sub-sector will benefit from this trade liberalization if some conditions to promote efficiency and to fair trade in international market could be realized.
Keywords: Essence and Impact, Trade Liberalization, Estate-Crop Sub-Sector, Strategic Business Environment